Mathematical Model Construction of Network Computer Test Automation System for College English Teaching - Sun, Wenjuan; Han, Ping; Pei, Shaohua (Scientific programming, 2022)
Networked education represents a development direction of educational reform, has become a feature of modern education, and has formed a new impetus to the development of education. The change from paper-and-pencil examinations to computer network-based machine examinations is not only a reform of the content and form of the University English Level 4 and 6 examinations, but also a reflection of the reform of the comprehensive assessment system and teaching philosophy of University English teaching. Promoting the development and construction of online college English examination systems in universities, applying machine examinations to various types of tests and formal examinations for college English teaching, and updating the college English question bank through continuous accumulation of professional teachers will have very high research value and practical value in improving the quality of examinations and promoting the standardization of college English examinations. In order to show the individualized chemistry report simultaneously, it is necessary to further ask relevant subject experts, educational measurement experts, and front-line teachers to expand the question attributes; that is, the question attributes extend to module specific knowledge points, cognitive levels, and information literacy ability levels, while most of the pages are combined with Ajax technology to reduce hardware resource dependency and optimize software performance. The paper analyzes the requirements analysis and overall design of the online college English examination system, including the design objectives, design principles, functional design, core algorithm design, architecture design, database design, and security design. The main functions of the online college English examination system, such as personal information management, question bank information management, test paper grouping management, online examination management, paper marking management, and system setting management, are discussed in detail. The main functions of the system, such as personal information management, question bank information management, test paper grouping management, online test management, mark and approve management, and system setting management, are discussed in detail, and the performance test and some function test of the system are also briefly discussed. The whole research process involves the identification of test questions and their attributes in the construction of the question bank, the construction of the adaptive test system, the comprehensive analysis of the mock test results, and the thinking about the application of the high school adaptive academic level test.